Les perspectives temporelles : les connaître pour en tenir compte dans nos interventions en promotion de la santé - Lessard, Lily (Global Health Promotion, 2012)
Résumé La modification des habitudes de vie pour adopter des comportements sains repose notamment sur la capacité des individus et des populations à estimer les conséquences à long terme des gestes accomplis aujourd’hui. Cette capacité peut cependant varier d’une personne à l’autre, notamment en raison des perspectives temporelles (PT) adoptées. Les PT réfèrent à la tendance d’une personne ou d’un groupe de personnes à orienter ses décisions en fonction d’une vision tournée vers le passé, le présent ou le futur. Cet article vise à démystifier le concept de PT et à comprendre leur construit, afin d’identifier différentes façons d’en tenir compte dans les interventions en promotion de la santé. L’influence des PT sur la santé est principalement liée à leur capacité d’agir sur la motivation des personnes à adopter et à maintenir certains comportements. Une attention particulière doit être portée aux personnes et aux populations dont les PT sont orientées vers le présent. Elles présenteraient un plus grand risque d’adopter des comportements délétères et seraient susceptibles d’être moins sensibles aux messages qui visent la modification de ces comportements que les personnes qui adoptent une PT orientée vers le futur. En ce qui concerne leur construit, les PT sont le fruit de différentes dynamiques psychologiques et des facteurs individuels (âge, sexe, état de santé) et environnementaux (milieu familial, statut socioéconomique, éducation, culture). Parmi les moyens présentés pour tenir compte des PT dans les interventions en promotion de la santé figurent la mise en valeur des avantages à court terme d’un changement de comportement qui vise des bénéfices à long terme pour la santé, la modulation de l’intensité du soutien à l’empowerment des communautés en fonction des PT adoptées et la permutation d’une PT orientée vers le présent vers une PT orientée vers le futur.
Keywords: Lessard_Lily

Comment communiquer le risque? Recherche-action sur le rôle du communicateur dans le cadre d’un projet de recherche - Kouri, Marylene; Motulsky, Bernard; Lessard, Lily (2022)
Ce projet de maîtrise vise à analyser le travail du professionnel en communication et le rôle qu’il peut jouer au sein d’un projet de recherche impliquant des experts dans le domaine de la santé communautaire, de la chimie marine et de la géographie. Plus précisément, il a pour objectifs de circonscrire les activités et les livrables de communication nécessaires au démarrage d’un projet de recherche, de déterminer comment communiquer le risque lorsque nous n’avons pas encore toutes les données et les solutions et il entend servir de modèle aux scientifiques pour une collaboration fructueuse et interdisciplinaire afin d’intégrer leurs communications aux travaux et au processus de recherche. Cette recherche-action entend suivre une équipe intersectorielle composée de huit chercheurs.euses et profesionnels.elles de recherche de l’Université du Québec à Rimouski (UQAR) et de l’Université du Québec à Montréal (UQAM). Cette équipe a pour mission d’étudier le phénomène de salinisation des puits côtiers au Bas-Saint-Laurent et en Gaspésie susceptible de s’accroître avec les changements climatiques. Il s’agit d’un projet de recherche financé par le Réseau Inondations InterSectoriel du Québec (RIISQ) et le Réseau Québec Maritime (RQM). L’objectif de la communication proposée est de présenter la méthodologie et les résultats préliminaires de cette recherche-action.
Keywords: Lessard_Lily

Vulnérabilités psychosociales des populations rurales du Québec en temps de pandémie - Lessard, Lily; Simard, Dominic; Morin, Marie-Hélène (Santé Publique, 2021)
Keywords: Lessard_Lily

Entendre et comprendre les expériences de désastre par la recherche narrative - Leclerc, Typhaine; Lessard, Lily; Saint-Charles, Johanne (Intervention, 2024)
Les événements météorologiques extrêmes (EME) et les désastres qu’ils entrainent provoquent des conséquences psychosociales qui sont modulées en fonction de différents facteurs sociaux. On constate aussi que les récits médiatiques et culturels qui circulent au sujet des EME ne sont pas représentatifs de l’ensemble des expériences de personnes sinistrées : celles qui en subissent les conséquences les plus sévères tendent aussi à être celles qu’on « entend » le moins dans l’espace public. Ces personnes sont ainsi susceptibles de vivre de l’injustice épistémique, ce qui a des effets délétères sur le soutien qu’elles reçoivent. Face à ces constats s’impose la nécessité de mieux comprendre la diversité des expériences d’EME et d’explorer des stratégies pour soutenir l’ensemble des personnes sinistrées dans leur rétablissement psychosocial. Cet article soutient que la recherche narrative peut contribuer à répondre à ces objectifs. En dépeignant des réalités multiples, la recherche narrative centrée sur les récits de personnes sinistrées présente aussi un intérêt significatif pour l’amélioration des pratiques d’intervention en contexte de désastre. , Extreme weather events (EWE) and their resulting disasters cause psychosocial consequences that are moderated by different social factors. Media and cultural accounts of EWEs do not represent the full range of disaster survivor experiences, that is, those who experienced the most severe consequences also tend to be those least “heard” in the public arena. These people are therefore most likely to experience forms of epistemic injustice that negatively impact the support offered to cope with disaster. Considering these findings, there is a need to better understand the diversity of EWE experiences and explore strategies for supporting all disaster survivors in their psychosocial recovery. This article argues that narrative research can help meet these needs. By portraying the multiple realities of people affected by EWEs, narrative research focusing on the stories of disaster survivors is also of significant interest for improving intervention practices in this context.

Intersectoral research and multi-risk approaches in Québec: systemic risk management and its psychosocial consequences - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Contribution paper to the Global Assessment Report on Disaster Risk Reduction, 2022)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.
Keywords: Boivin_Maxime; Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Lessard_Lily; Site_internet_RIISQ

Intersectoral approaches: the key to mitigating psychosocial and health consequences of disasters and systemic risks - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Disaster Prevention and Management: An International Journal, 2023)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.
Keywords: Boivin_Maxime; Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Infolettre; Infolettre_Fevrier_2023; Lessard_Lily; Site_internet_RIISQ